2018
DOI: 10.1111/phn.12553
|View full text |Cite
|
Sign up to set email alerts
|

The attitudes of refugee women in Turkey towards family planning

Abstract: Objectives This study was conducted to determine refugee women's attitudes towards family planning and related factors. Design and Sample Designed in descriptive and cross‐sectional type, the study involved 555 voluntary Syrian refugee women in Turkey. Measures A questionnaire and the Family Planning Attitude Scale (FPAS) were used. Independent Sample T test, ANOVA test, and Pearson's correlation analysis were used for data analysis. Results A significant association was found between the average FPAS scores w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
18
1
3

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 14 publications
0
18
1
3
Order By: Relevance
“…Non-probability methods are more feasible while conducting research with some marginalized populations, especially in situations with limited resources and research capacity. However, non-probability sampling results in findings that are less representative of the population and less generalizable across settings (29, 30). Additionally, some of the non-random samples within our review were very small, further reducing their generalizability (31).…”
Section: Discussionmentioning
confidence: 99%
“…Non-probability methods are more feasible while conducting research with some marginalized populations, especially in situations with limited resources and research capacity. However, non-probability sampling results in findings that are less representative of the population and less generalizable across settings (29, 30). Additionally, some of the non-random samples within our review were very small, further reducing their generalizability (31).…”
Section: Discussionmentioning
confidence: 99%
“…In Syria, the fertility rate was reported to be 2.68 in 2014 and 2.55 in 2015 (Indexmundi, 2016), whereas in Turkey, it was stated to be 2.15 in , 2.11 in 2016and 2.07 in 2017(TSI, 2017. Studies have found that Syrian refugee women have more children after migration (Bayram Deger, Ertem, Durmuş, Cifci, & Balci, 2018) and that migration has no negative effect on their fertility (Alan Dikmen et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…In this study, the proportion of Syrian refugee women who used some kind of FP method was 75.1%, and 47.9% used a traditional FP method. Similarly, although Karakaya et al (2017) reported that Syrian refugee women stated that the most used FP method was withdrawal (coitus interruptus), other studies have found that modern FP methods were most used (Alan Dikmen et al, 2019;Benage, Greenough, Vinck, Omeira, & Pham, 2015;Smith, 2016). For this reason, it may be said that it will be difficult to generalize the use of FP methods in refugees and that there are many factors which affect this.…”
Section: Factors Regarding Practices Concerning Fpmentioning
confidence: 99%
See 2 more Smart Citations